Case Report: A Very Low Birth Weight Female Infant With Congenital Bilateral Periventricular Leukomalacia, Born to a Mother With Coronavirus Disease 2019 - Kobata, Keisuke; Yutaka, Nanae; Ogasawara, Hiroshi; Mima, Aya; Suzuki, Kaho; Hazama, Ryoichi; Goldman, Ran D.; Nabetani, Makoto (Frontiers in Pediatrics, 2022)
A 26-year-old primipara woman with COVID-19 performed an emergency Caesarean section due to further hypoxemia at 28 weeks 5/7 days gestation. The female neonate was born weighing 1347 gram with an Apgar score of four at 1 minute, three at 5 minutes, and eight at 10 minutes. RT-PCR from nasopharyngeal swabs for COVID-19 were performed at birth, 24 hours, and 48 hours after birth, all of which were negative. On head ultrasound bilateral cystic lesions were found in the anterior horn of the lateral ventricles at birth. A brain magnetic resonance imaging (MRI) test at 56 days of life (corrected 36 weeks and 6/7 days) revealed cystic lesions with T1 low signal, T2 high signal, and T2 Flair high signal around the anterior horn of the lateral ventricle and We diagnose it as Grade 2 periventricular leukomalacia (PVL). She was discharged on day 64 of life, with no abnormality on exam. While the majority of neonates born to women with COVID-19 during pregnancy have favorable outcome, we report a case of a neonate with Grade 2 periventricular leukomalacia and this should prompt clinicians to monitor fetal cerebral function and structure shortly after birth.